Analisis Penipuan Digital (Cyber Fraud) Tantangan Dan Solusi Dalam Era Transformasi Digital : Analysis Of Digital Fraud (Cyber Fraud) Challenges And Solutions In The Era Of Digital Transformation - Pahrudin, Pajar; Yulindawati (Jurnal Riset Inossa : Media Hasil Riset Pemerintahan, Ekonomi dan Sumber Daya Alam, 2025)
Abstract The purpose of this study is to explore the phenomenon of digital fraud (cyber fraud), examining its nature, prevalence, and impact on individuals and organizations in the digital landscape. This research employs a qualitative approach, utilizing case studies and interviews with victims of cyber fraud, cybersecurity experts, and law enforcement officials. Data was collected through structured interviews and analyzed thematically to identify common patterns and insights related to the tactics used by cyber fraudsters and the effectiveness of preventive measures. The findings reveal that cyber fraud is increasingly sophisticated, utilizing advanced technology and social engineering tactics to deceive victims. Key factors contributing to the rise of cyber fraud include the rapid digitalization of services, lack of awareness among users, and inadequate cybersecurity measures. The study also highlights the emotional and financial toll on victims, as well as the challenges faced by law enforcement in addressing these crimes. This study contributes to the existing literature by providing a comprehensive analysis of cyber fraud from multiple perspectives, including victim experiences and expert insights. It emphasizes the need for enhanced public awareness campaigns and stronger cybersecurity practices to mitigate the risks associated with digital fraud, offering valuable recommendations for individuals and organizations to safeguard against such threats. Keywords: Cyber ​​Fraud, Digital Transformation, Security Challenges